2007
DOI: 10.1080/17518250701756983
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic synthesis of chiral heteroaryl alcohols using plant fragments as the only biocatalyst and reducing agent

Abstract: The enzymatic reduction of prochiral heterocyclic ketones by carrot (Daucus carota) root in water afforded the corresponding S-alcohols in accordance with the Prelog's rule. The reaction was performed under various conditions in order to optimize the procedure of bioreduction regarding reaction time, yield, and optimal mass of carrot. The optimized procedure was used to test the ability of other plants to carry out the reaction. In the latter experiment, it was observed that, with regard to stereospecificity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 25 publications
0
5
1
Order By: Relevance
“…Moreover, 50% of the unwanted enantiomer always occurs at kinetic resolution. Aldabalde et al performed the asymmetric reduction of substrate 1 using the D. carota biocatalyst in a shorter reaction time than our study, but their ee and yield were lower than our yield and ee . Salvi et al carried out the asymmetric reduction of substrate 1 using R. arrhizus biocatalyst in a longer reaction time, lower ee and yield than our study .…”
Section: Resultscontrasting
confidence: 65%
See 2 more Smart Citations
“…Moreover, 50% of the unwanted enantiomer always occurs at kinetic resolution. Aldabalde et al performed the asymmetric reduction of substrate 1 using the D. carota biocatalyst in a shorter reaction time than our study, but their ee and yield were lower than our yield and ee . Salvi et al carried out the asymmetric reduction of substrate 1 using R. arrhizus biocatalyst in a longer reaction time, lower ee and yield than our study .…”
Section: Resultscontrasting
confidence: 65%
“…The Rhizopus arrhizus mediated bioreduction of 1‐(benzofuran‐2‐yl)ethanone furnished 99.3% ( S )‐1‐(benzofuran‐2‐yl)ethanol, with 91.7% ee . In the literature, it has been reported that 1‐(benzofuran‐2‐yl)ethanone is reduced to ( R )‐benzofuran alcohol by 95% ee and 47% yield with Daucus carota as biocatalyst . In the present study, isolated Lactobacillus paracasei BD87E6 was employed as a whole‐cell biocatalyst in the asymmetric bioreduction of 1‐(benzofuran‐2‐yl)ethanone to ( S )‐1‐(benzofuran‐2‐yl)ethanol in an aqueous medium (Figure ).…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…[20,21]. When compared to earlier reports [22][23][24][25], the present study demonstrates that the dehydrogenase enzymes present in D.carota has reduced keto groups attached to five member heteroaryl compounds (1h -1j) (pyrrole, furan and thiophene) with good enantio-selectivity. thus demonstrating the broad specificity of the dehydrogenase enzyme present in the carrot.…”
Section: Resultsmentioning
confidence: 68%
“…Plant biocatalysts have been applied primarily in the reduction of ketones. [8][9][10][11][19][20][21][22][23][24][25]. Biooxidation of alcohols has been described much less [8,[12][13][14][15]22].…”
Section: Introductionmentioning
confidence: 99%